A model-based PID-like motion control method for flexible-joint manipulator with harmonic drives. (December 2021) - Yang, Guocai; Liu, Yechao; Ji, Junhong; Jin, Minghe; Piao, Songhao
A novel control method is proposed to achieve high trajectory tracking precision, for flexible-joint manipulators. The method consists of three major parts: joint torque generator, joint torque tracker and motor position controller. The expected torque is generated by a PID controller based on the manipulator's rigid dynamics model. In the torque tracker, motor position is corrected in both feedback and feedforward ways. Finally, the motor position controller is responsible to track the corrected motor trajectory to achieve the torque and position control. To suppress nonlinear friction, a disturbance observer is also implemented. The method is verified with a seven-DOFs manipulator. Simulation and experimental results show that, the proposed method is efficient and practical to suppress vibration caused by flexible transmission and disturbance due to friction. As result, high positioning accuracy is achieved in a certain wide working speed range. The no-load motion accuracy is better than 0.6 mm with a manipulator whose length is 1.8 meter, and the motion error is less than 3 mm with loading of four kilograms.